Tender : a cook and his vegetable patch - Slater, Nigel (Ten Speed Press, 2011)
"A comprehensive, deeply personal, and visually stunning guide to growing and cooking vegetables from Britain's foremost food writer, with more than 400 recipes and extensive gardening notes. Tender is a cookbook, a primer on produce, and above all, a beloved author's homage to his favorite vegetables. The chapters explore 29 vegetables and offer enticing, comforting recipes such as Potato Cakes with Chard and Taleggio, a Tart of asparagus and Tarragon, and Grilled Lamb with Eggplant and Za'atar"--